Ekstrak Secang sebagai Bahan Diuretikum (Percobaan terhadap Tikus Putih Jantan Galur Spraque Dawley) - Pertamawati Pertamawati; Nuralih Nuralih; Fahri Fahrudin (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2014)
Empirically, secang (Caesalpinia sappan L.) utilized as natural materials to overcome various types of disease but not yet known how the influence of consuming secang against the volume urine. The experiment was conducted on white male rats varian Spraque dawley and sample test extract ethanol 96% of dried bark secang. The animal try grouped in seven groups and each group consists of six animal try, namely normal group, positive group (furosemide 10 mg/200 g BW), negative group (water 2 ml/200 g BW), Group of I dose (62,5 mg/kg BW), dosage II (125 mg/kg BW), dosage III (250 mg/kg BW), and dosage IV (500 mg/kg BW). Thirty minutes after granting test sample, the animal try given drinking water 2 ml/200 g BW by gastric sonde, then put them in metabolite cages for 16 hours (overnight). The result of experiment conducted show the average volume urine of animal try of normaly group was 4,5 ml, negative group was 4,25 ml, dosage I was 4,5 ml, dosage II was 8 ml, Dosage III was 5,75 ml and dosage IV was 5,5 ml. The volume of animal try urine in the group II was the highest, so it can be said that secang extract (dosage II – 125 mg/kg BW) can be used as diureticum material.